Tinjauan Hukum Keluarga Islam terhadap Pelepasan Tanggung Jawab Orang Tua Mengasuh Anak pada Pasangan yang Bercerai: Studi di Desa Karang Anyar Kecamatan Selagai Lingga Kabupaten Lampung Tengah - Deni Pratama; Hepi Riza Zen; Idrus Alghiffary (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Parental divorce is often followed by a relinquishment of childcare responsibilities. This study aims to analyze the practice of parental responsibility for childcare after divorce and examine it from the perspective of Islamic family law and positive Indonesian law. This study uses an empirical method with a sociological juridical approach through interviews, observations and documentation. The results of the study show that childcare is de facto transferred to grandparents without formal legal determination, due to economic, occupational and remarriage factors, this practice creates a gap between legal norms and social reality. Despite the age and economic limitations of parenting, grandparents are able to meet the basic needs and moral development of children. In Islamic law, the transfer is justified based on the benefit of the child, but the obligation of maintenance remains attached to the biological parents. The analysis of Maqasid Syariah shows that this practice is in line with the purpose of Islamic law. This research contributes to strengthening the understanding of the importance of legal certainty and the protection of children's rights.